Response to the engineer’s reply concerning evaluation for additional work of sharing pile work in zone B - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the response to the engineer’s reply concerning evaluation for additional work of sharing pile work in zone B of BRACU new campus development project.